Altered phenotype and function of NK cells infiltrating human papillomavirus (HPV)-associated genital warts during HIV infection - Bere, Alfred (Clinical immunology (Orlando, Fla.), 2014)
Copyright © 2013 Elsevier Inc. All rights reserved.